A 3‐dimensional‐printed patient‐specific guide system for minimally invasive plate osteosynthesis of a comminuted mid‐diaphyseal humeral fracture in a cat. Issue 3 (15th February 2018) - Oxley, Bill
Abstract: Objective: To report the use of a 3‐dimensional (3D)‐printed patient‐specific reduction guide system to facilitate minimally invasive plate osteosynthesis (MIPO) of a humeral fracture in a cat. Study design: Case report. Animals: A 9‐year‐old male neutered domestic short hair cat weighing 4.4 kg. Methods: A 9‐year‐old male domestic short hair cat was presented with a comminuted, mid‐diaphyseal left humeral fracture. Computed tomographic data were processed to yield 3D mesh representations of both humeri and subsequently manipulated in computer‐aided design software. The mirrored, intact humerus was used as a template for appropriate spatial orientation of the major proximal and distal fracture fragments. Patient‐specific Ellis pin orientation guides and a reduction guide were designed and 3D printed. The guide system was used intraoperatively to align the major fracture fragments before application of locking internal fixation via standard MIPO surgical portals. Results: Internal fixation of the fracture resulted in appropriate bone alignment. Recovery was uncomplicated, with early return to normal limb function and radiographic evidence of advanced fracture healing after 4 months. Conclusion: A 3D‐printed patient‐specific reduction guide system facilitated accurate alignment of a comminuted humeral fracture during MIPO without intraoperative imaging.